Molecular cytogenetic study of heterochromatin in Hisonotus leucofrenatus (Teleostei, Loricariidae, Hypoptopomatinae) - Andreata, Artur Antonio [UNESP]; Ferreira, Daniela Cristina [UNESP]; Foresti, Fausto [UNESP]; Oliveira, Claudio [UNESP] (Wiley-Blackwell Publishing, Inc, 2010)
The fish species Hisonotus leucofrenatus exhibits a large amount of C-band positive segments with different responses after application of the C-banding technique. Type I class named herein appeared to be heavily stained after C-banding in the terminal position of five chromosome pairs and type II class, weakly stained after C-banding in the interstitial or pericentromeric position in nine chromosome pairs and in the supernumerary chromosomes. No variation was observed in type II C-band positive segments, however, type I segments displayed conspicuous polymorphisms, and six cytotypes were detected among the fish analyzed. Chromosomes were also analyzed by CMA(3) and DAPI staining, which showed that type I C-band positive segments comprised both AT-rich and GC-rich DNA, while type II segments were mainly composed of GC-rich sequences. HindIII-digested genomic DNA exhibits fragments of the ladder-like pattern, characteristic of tandemly arrayed repetitive sequences. Two of those fragments corresponding to monomeric and dimeric units of a 78 bp repetitive DNA sequence were cloned and sequenced. The cloned repetitive DNA was used as probe in fluorescent in situ hybridization experiments. The results revealed that these sequences were located in the same position as the type I C-band positive segments. This satellite DNA did not hybridize with DNA from other species of Hisonotus or from other fish of the family Loricariidae, suggesting that this sequence is specific to H. leucofrenatus. The role of these repetitive sequences in the karyotypic evolution of this species is discussed.